Brief analysis of foreign experience in arrangement of purchasing weapons and military equipment - Oleg V. Savchenko (Krylov State Research Centre, 2021)
Object and purpose of research. The paper provides a detailed analytical review of the state procurement systems for weapons, military and special-purpose equipment, supplies and services to support military forces of five states, which are world leaders in the military field: USA, UK, France, Germany and China. A special emphasis is made on shipbuilding. Subject matter and methods. The review is based on modern strategic documents and legislative acts regulating the pro-curement activities of major state military agencies. Main results. A detailed consideration is given to specific procurement systems operating in foreign countries, similar features and differences are identified, national specifics are mentioned. Recommendations are given regarding lessons to be learned by Russian military departments. Conclusion. Based on the foreign experience it is found advisable to combine centralized purchasing of major military products and equipment and decentralized procurement of some general-purpose items.